The Library - Lang, Andrew, 1844-1912 (Salt Lake City, UT : Project Gutenberg, 1999)
"The Library" by Andrew Lang is a book published in the late 19th century as part of the "Art as Home" series. This charming guide explores the art of book-collecting for amateur bibliophiles, blending practical advice with passionate defense of the collector's craft. Lang examines book-hunting as both sport and obsession, offering wisdom on building collections, preserving treasured volumes, and understanding why books remain our most enduring friends. Through wit and warmth, he captures the joys, sorrows, and "gentle-madness" that define the bibliophile's world. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Library_(book)
Release date is 1999-12-01
Transcribed from the 1881 Macmillan and Co. edition by David Price
Keywords: Books; Book collecting